Ahmad Dhani’s Legal Case: a Forensic Linguistic Study of Defamation - Arimi, Sailal; Adelawati, Munzila (SUAR BETANG, 2024)
This forensic linguistics study aims to evaluate whether the prosecutors of the South Jakarta and Surabaya District Courts in the case of hate speech committed by Ahmad Dhani (AD) are in accordance with the Electronic Information and Transaction Law (ITE Law) Number 11 of 2018 and ITE Law Number 19 of 2016. In addition, this research also aims to determine the qualifications of hate speech in AD's case. Data was collected through the documentation method, which includes collecting data that has been circulating in the community online, following the legal process written in the South Jakarta and Surabaya Case Tracking Information System (SIPP), and looking at the results of the District Court decisions that have been legally binding (Inkracht) Number 370/Pid.Sus/2018/PN JKT.SEL and Number 275/Pid.Sus/2019/PN Sby. After the data was collected it was analyzed using a forensic linguistic approach. The language data of the legal case was analyzed through the approach of the internal structure of language, namely semantics, and the external structure of language which includes sociolinguistics and pragmatics. The results of this study show that the speech used by AD has negative diction and can demean his speech partners, then the prosecutor's charges against AD were not found to abuse the 2016 ITE Law and there were no rubber articles that caused multiple interpretations. AbstrakKajian linguistik forensik ini bertujuan mengevaluasi apakah tuntutan jaksa Pengadilan Negeri Jakarta Selatan dan Surabaya dalam kasus ujaran kebencian yang dilakukan oleh Ahmad Dhani (AD) sesuai dengan Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) Nomer 11 Tahun 2018 dan UU ITE Nomor 19 Tahun 2016. Selain itu, penelitian ini juga bertujuan menentukan kualifikasi ujaran kebencian dalam kasus AD. Data dikumpulkan melalui metode dokumentasi, yang meliputi pengumpulan data yang telah beredar di masyarakat secara daring, mengikuti proses hukum yang tertulis di Sistem Informasi Penelusuran Perkara (SIPP) Jakarta Selatan dan Surabaya, dan melihat hasil putusan Pengadilan Negeri yang telah berkekuatan hukum tetap (Inkracht) Nomer.370/Pid.Sus/2018/PN JKT.SEL dan Nomer.275/Pid.Sus/2019/PN Sby. Setelah data terkumpul, analisis dilakukan menggunakan pendekatan  linguistik forensik. Data bahasa berkasus hukum tersebut dianalisis melalui pendekatan struktur internal bahasa, yaitu semantik, dan struktur eksternal bahasa yang mencakup sosiolinguistik dan pragmatik. Hasil penelitian ini menunjukkan bahwa tuturan yang digunakan AD memiliki diksi negatif dan dapat merendahkan mitra tuturnya. Dalam tuntutan jaksa kepada AD tidak ditemukan penyalahgunaan UU ITE 2016 dan tidak terdapat pasal karet yang menyebabkan multitafsir.